Perceptions of Teacher Leadership within the New Tech High School Model - Bradley-Levine, Jill; Mosier, Gina; Perkins, Tyonka (International Journal of Teacher Leadership, 2014)
This study examines teacher leadership within the framework of a specific school reform model, focusing on an empowered school culture, including teacher involvement in curriculum and instruction, school policy decisions, and professional development activities. Using a concurrent triangulation mixed methods design, data were collected through a teacher survey and teacher and administrator interviews. Findings show that reform implementation affects teachers' perceptions of teacher leadership activities and opportunities.